Efficiency and portability: Guidelines to develop websites - Chiuchi, Cleriston Araujo [UNESP]; De Souza, Rogéria Cristiane Gratão [UNESP]; Santos, Adriana Barbosa [UNESP]; Valêncio, Carlos Roberto [UNESP] (My University, 2011)
The use of the Internet as a means of ensuring greater visibility for products, services and information offered by companies is gaining strength in recent decades. However, it is known that to ensure satisfaction and subsequent virtual customer loyalty, it is necessary to guarantee the quality of the websites, allowing indiscriminate access regardless of the resources used, as well as rapid responses to possible requests. In order to assist this process, this paper presents a set of guidelines for the development of websites having quality characteristics, efficiency and portability as per ISO 9126 norms. An observational analysis of e-commerce websites was done which showed that they are inadequate as to the proposed guidelines, making them difficult to access available content. Therefore, the adoption of the proposed guidelines can greatly contribute to increasing the quality of websites and, consequently, enable quick and effective access regardless of the resources used.
Keywords: Efficiency and portability characteristics; Websites development guidelines; Websites quality assurance; Customer loyalty; Observational analysis; Quality characteristic; Rapid response; Customer satisfaction; Efficiency; Knowledge engineering; Quality assurance; Software engineering; Computer software portability